Correlation of Age, Weight and Body Mass Index with Bone Mineral Density using Dual–Energy X-ray Absorptiometry–Initial Experience in INMAS, Bogura (Bangladesh Journal of Nuclear Medicine, 2025)
Objectives: Worldwide osteoporosis is the major public health concern among the aging population. Body weight & Body Mass Index (BMI) are inversely related with the risk of the osteoporotic fractures. Low bone mineral density (BMD) is also a major risk factor for osteoporosis & its related fractures. Osteoporosis is becoming a burning issue within the elderly group of Bangladesh. There are several studies that have shown the significant relationship of age, body weight and BMI with BMD. Therefore, the objective of the recent study is to establish the relationship of age, weight and BMI with BMD, in patients attending for DEXA scan at INMAS Bogura. Patients and methods: The cross-sectional observational study was carried out at INMAS Bogura from August 2023 to February 2024. A total of 64 patients referred for BMD estimation by DEXA scan, were included in this study. Result: In this study among 64 patients about 31.25% were male and 68.75% were female. About 20.31% were underweight, 40.62% were normal, 23.07% were overweight and 14.00% were obese. Less than 60 years of age were 48.43% and ≥60 years of age were 51.56%. In the right femur 40.62% were normal BMD, whereas 59.37% were low BMD. In the case of the left femur 46.87% were normal and 53.12% were low BMD. In spine BMD 23.47% were normal and 76.56% were low BMD. Moderate positive Pearson’s correlation is found in between BMI with right femur T score (r= 0.43; p=